Eksplorasi, Isolasi, dan Identifikasi Jamur Entomopatogen Asal Rizosfer Tanaman Padi - Chaieydha Noer Afiefah; Nani Kitti Sihaloho; Yudhan Saylendra Anugratama; Naili Arzaqul Barokah (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
Rice pest management in the field predominantly depends on the application of chemical pesticides. However, the use of entomopathogenic fungi represents an alternative strategy within Integrated Pest Management (IPM) programs. This study aimed to examine the relationship between soil organic matter content and soil pH with the presence of entomopathogenic fungi, as well as to identify these fungi morphologically from the rhizosphere of rice plants using the bait insect method. The research was conducted from July to October 2025 and involved several stages, including soil sampling and analysis, isolation and collection of entomopathogenic fungi, morphological identification, and data analysis. Soil samples were collected from the regencies of Blora, Jepara, Kebumen, and Semarang. The results indicated that the soil samples were categorized into low, medium, and high organic carbon levels, with soil pH ranging from 6.50 to 7.99. Morphological identification revealed that Aspergillus sp. was present in isolates coded BB1, BB2, KK1, KK3, SA2, and SA3, showing both microscopic and macroscopic characteristics consistent with established references. The detection of entomopathogenic fungi in the rice rhizosphere highlights their ecological role in maintaining agroecosystem balance and their potential to naturally suppress pest populations. Nevertheless, molecular identification is required to accurately determine the fungal species prior to conducting further evaluations, such as pathogenicity, virulence, and efficacy tests against target pests, before large-scale application can be considered